2013
DOI: 10.1063/1.4802178
|View full text |Cite
|
Sign up to set email alerts
|

BFKL, BK and the infrared

Abstract: The perturbative non-linear (NL) effects in the small-x evolution of the gluon densities depend crucially on the infrared (IR) regularization. The IR regulator, R c , is determined by the scale of the non-perturbative fluctuations of QCD vacuum. From the instanton models and from the lattice R c ∼ 0.3 fm. For perturbative gluons with the propagation length R c = 0.26 fm the linear BFKL gives a good description of the proton structure function F 2 (x, Q 2 ) in a wide range of x and Q 2 . The NL effects turn out… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…At superhigh energies, E Lab > 10 4 − 10 5 GeV, the perturbative component starts taking over and its unitarization becomes a central issue. In [8,9,10] it was demonstrated that the non-linear, i.e., unitarity effects are very sensitive to the IR regularization which defines a transition between the nonperturbative and perturbative domains. Empirically, the bulk of the total cross section at E Lab ∼ 10 4 −10 5 GeV comes from the nonperturbative domain and our analysis suggests rather small, infrared cutoff for the perturbative contribution, R c = 0.26 fm.…”
Section: Vacuum Color Screening and CD Bfklmentioning
confidence: 99%
See 1 more Smart Citation
“…At superhigh energies, E Lab > 10 4 − 10 5 GeV, the perturbative component starts taking over and its unitarization becomes a central issue. In [8,9,10] it was demonstrated that the non-linear, i.e., unitarity effects are very sensitive to the IR regularization which defines a transition between the nonperturbative and perturbative domains. Empirically, the bulk of the total cross section at E Lab ∼ 10 4 −10 5 GeV comes from the nonperturbative domain and our analysis suggests rather small, infrared cutoff for the perturbative contribution, R c = 0.26 fm.…”
Section: Vacuum Color Screening and CD Bfklmentioning
confidence: 99%
“…absorption corrections to the BFKL evolution are described by the non-linear BK equation [6,7]. The strength of non-linear effects depends crucially on the IR cutoff R c [8,9,10]. Hence, one more issue we address in this communication is the role of the absorption corrections to σ pp tot and the non-linear dynamics of the perturbative component of pp-interactions at the LHC energies.…”
Section: Introductionmentioning
confidence: 99%